2022
DOI: 10.32322/jhsm.1130930
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 fear on hygiene behaviors in hemodialysis patients during the COVID-19 pandemic

Abstract: Aim: Current study aims to specify the fear levels and hygiene habits of hemodialysis (HD) patients infected or not infected with coronavirus disease 2019 (COVID-19) in the course of the COVID-19 pandemic. Material and Method: This study was performed between 15-30 April 2021 as a case-control study whose population consisted of 124 dialysis patients treated in the dialysis unit of Batman Education and Research Hospital. In the dialysis unit, while 25 HD patients who were not present with COVID-19 were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…This is consistent with Corbett and coworkers [7] , which also had a higher prevalence of COVID-19 in ESRD (19.6%). At the same time, the lowest COVID-19 prevalence was reported in Turkey; Kemeç and coworkers [8] reported that it was 0.2%, which was against our results. In ESRD, high temperature (71.3%), dry cough (61.8%), general fatigue (54.4%), loss of smell (52.2%), and dizziness (53.7%) were significantly higher in non-ESRD COVID-19 patients compared to ESRD COVID-19 patients.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with Corbett and coworkers [7] , which also had a higher prevalence of COVID-19 in ESRD (19.6%). At the same time, the lowest COVID-19 prevalence was reported in Turkey; Kemeç and coworkers [8] reported that it was 0.2%, which was against our results. In ESRD, high temperature (71.3%), dry cough (61.8%), general fatigue (54.4%), loss of smell (52.2%), and dizziness (53.7%) were significantly higher in non-ESRD COVID-19 patients compared to ESRD COVID-19 patients.…”
Section: Discussioncontrasting
confidence: 99%